Methionine enkephalin upregulates toll-like receptors in macrophages to suppress severe fever with thrombocytopenia syndrome virus infection - Tian, Jing; Ma, Zhuping; Wang, Xiaomeng; Li, Yonggang; Mu, Yulian; Tao, Xiaoli (Frontiers in Immunology, 2025)
BackgroundSevere fever with thrombocytopenia syndrome virus (SFTSV) is a newly identified tick-borne virus with a high case fatality rate. Currently, no specific antiviral drugs are available for its treatment. Methionine enkephalin (MENK) has the ability to enhance immune cell function nonspecifically. This study investigated the mechanism by which MENK regulates macrophages to exert antiviral effects against SFTSV infection.MethodsAn SFTSV-infected RAW264.7 macrophage model pretreated with MENK was developed. RNA sequencing was employed to analyze transcriptomic alterations and identify differentially expressed genes (DEGs). Subsequent experimental validation based on bioinformatics analysis was performed on key DEGs.ResultsThe DEGs between the MENK–SFTSV and SFTSV groups were mainly enriched in several signaling pathways, including the Toll-like receptor (TLR) signaling pathway (ko04620), IL-17 signaling pathway (ko04657), TNF signaling pathway (ko04668), and interaction between viral proteins and cytokines and their receptors (ko04061). Key genes included TLR7, TLR3, TLR8, TLR9, activator protein-1 (AP-1), IL-17RA, TNF-α, IL-1β, CCR5, and CXCL10, all of which successfully docked with the MENK molecule. Compared with the TLR7 agonist imiquimod (IMQ), MENK demonstrated a greater advantage in modulating macrophages to resist SFTSV infection. MENK and the TLR7 agonist imiquimod can upregulate the expressions of TLR7, TLR3, AP-1, and IL-17RA. In addition, MENK significantly upregulated the levels of TLR9, TLR8, IL-1β, TNF-α, CCR5, and CXCL10.ConclusionMENK upregulated the expression levels of the pattern recognition receptors and cytokine receptors; promoted the nuclear transcription to modulate cellular immune responses; and increased the levels of the cytokines to induce inflammatory responses against SFTSV infection. Notably, MENK possessed unique advantages and exhibited efficacy comparable to IMQ in restoring antiviral immunity, suggested that MENK emerged as a promising host-directed therapeutic candidate or vaccine prototype against SFTSV infection, warranting further preclinical and clinical investigation.